Manfaat Terapi Musik bagi Lansia yang Mengalami Depresi dan Gangguan Kognitif - Nurmalaningsih, Ucik; Haryanto, Joni; Fauziningtyas, Rista; Choiriyah, Lilik; Basri, Basri (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effectiveness of music therapy in elderly with cognitive impairment who experience depression in the Nursing Home. The research method uses a systematic review review following the principles of PRISMA 2020. The article selection process follows the PICO structure. MeSH is used for keyword searches in the medical field. In assessing the bias and methodological quality of the articles obtained, this study uses the Joanna Briggs Institute (JBI) critical assessment. The results of the study indicate that music therapy interventions in the elderly are able to manage emotions and have a good impact on the elderly with depression. In addition, music intervention therapy with a time span of 30-40 minutes for 8-12 weeks can help the elderly with cognitive disorders such as dementia. The elderly who receive music intervention therapy are considered able to control emotional regulation, foster empathy and their creativity. Keywords: Depression, Intervention, Elderly, Music Therapy